An experimental model of chronic severe mitral regurgitationCentral MessagePerspective - Martha M.O. McGilvray, MSt, MD, MPHS; Tari-Ann E. Yates, MD; Lynn Pauls, MD; Meghan O. Kelly, MD; Nicholas Razo, BS; Stacie McElligott, BAS, RVTg, RLAT; Glenn J. Foster, RT(R, MR); Jie Zheng, PhD; Jonathan K. Zoller, MD; Christian Zemlin, PhD; Ralph J. Damiano, Jr., MD (JTCVS Techniques)
Objective: To develop a minimally invasive, reproducible model of chronic severe mitral regurgitation (MR) that replicates the clinical phenotype of left atrial (LA) and left ventricular dilation and susceptibility to atrial fibrillation. Methods: Under transesophageal echocardiographic guidance, chordae tendinae were avulsed using endovascular forceps until the ratio of regurgitant jet area to LA area was ≥70%. Animals survived for an average of 8.6 ± 1.6 months (standard deviation) and imaged with monthly transthoracic echocardiography (TTE). Animals underwent baseline and preterminal magnetic resonance imaging. Terminal studies included TTE, transesophageal echocardiography, and rapid atrial pacing to test inducibility of atrial tachyarrhythmias. Results: Eight dogs underwent creation of severe MR and interval monitoring. Two were excluded—one died from acute heart failure, and the other had resolution of MR. Six dogs underwent the full experimental protocol; only one required medical management of clinical heart failure. MR remained severe over time, with a mean terminal regurgitant jet area to LA area of 71 ± 14% (standard deviation) and regurgitant fraction of 52 ± 11%. Mean LA volume increased over 130% (TTE: 163 ± 147%, P = .039; magnetic resonance imaging: 132 ± 54%, P = .011). Mean left ventricular end-diastolic volume increased by 38 ± 21% (P = .008). Inducible atrial tachyarrhythmias were seen in 4 of 6 animals at terminal surgery, and none at baseline. Conclusions: Within the 6 dogs that successfully completed the full experimental protocol, this model replicated the clinical phenotype of severe MR, which led to marked structural and electrophysiologic cardiac remodeling. This model allowed for precise measurements at repeated time points and will facilitate future studies to elucidate the mechanisms of atrial and ventricular remodeling secondary to MR and the pathophysiology of valvular atrial fibrillation.